Gramophone, Masinatahikan – Typewriter, Press, Our Mother(s) Tongue: Reflections on Indigenous (First Nations and Métis) Literacies and Media - Bell, Gloria Jane (KULA, 2021)
This essay discusses a wide range of media—including an 1853 Albion Cree Press, a Cree typewriter, and contemporary Indigenous artworks—to create a sense of the multiplicity of Indigenous technologies available for study today and the vastness of the visual record. While older art historical studies would be limited to so-called high art, namely paintings and sculpture, this essay takes an expansive approach to consider multiple examples of visual culture in the formation of Indigenous literacy traditions. The work considers the importance of birchbark biting and moss in the pictorial record, for example, as a form of Indigenous technology. This essay has also been inspired by recent conversations with my mom and colleagues in the discipline of contemporary art and for that I am thankful and try to reflect a more conversational approach to the media discussed herein as a methodology of upending binaries and tensions of spoken and unspoken and not-as-yet written stories. The research engages in visual analysis of Indigenous literary artifacts and images. By Indigenous literacies I mean the way Indigenous people have engaged and engage technologies and media to move ideas forward, to create art and culture. The essay takes a speculative approach, using some stories about artworks and narrative approaches to honor a history of Métis and Cree paths to knowledge that are based on storytelling rather than definitive histories. As a person of Métis ancestry on my maternal side, I write this essay not as a fluent Cree or Michif speaker, but as one who is in a life-long process of language learning. Analysis of visual imagery expands staid notions and simplistic understandings of Indigenous literacies as solely based on writing.